2018
DOI: 10.32598/irj.16.4.395
|View full text |Cite
|
Sign up to set email alerts
|

Psychoeducation on Improving Mental Health Literacy and Adjustment to Illness in Patients With Type 2 Diabetes: An Experimental Stud

Abstract: The present study investigated the role of psychoeducation in improving mental health literacy and adaptation in patients with type 2 diabetes. Methods: The present study was an interventional study with pre-test, post-test and follow-up design with a control group. The study population included patients with type 2 diabetes who referred to Iran Hospital. Based on the research method and considering the missing data, a sample size of 80 people was considered. In total, 40 patients were selected as the interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Therefore, designing and implementing effective interventions such as appropriate educational programs seems to be necessary, as most studies, such as Sayarifard et al [26], Noroozi et al, Bragg et al, Yu et al and Mahfouz et al [5, 10, 14, 34] have emphasised the urgent need for educational interventions. The effectiveness of such educational interventions has also been confirmed by Karimpour Vazifekhoran et al, Yu et al, and Perry et al [10, 25, 35]. The roles of the educational system and the mass media are very important in this regard.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Therefore, designing and implementing effective interventions such as appropriate educational programs seems to be necessary, as most studies, such as Sayarifard et al [26], Noroozi et al, Bragg et al, Yu et al and Mahfouz et al [5, 10, 14, 34] have emphasised the urgent need for educational interventions. The effectiveness of such educational interventions has also been confirmed by Karimpour Vazifekhoran et al, Yu et al, and Perry et al [10, 25, 35]. The roles of the educational system and the mass media are very important in this regard.…”
Section: Discussionmentioning
confidence: 82%
“…In another study, Karimpour Vazifekhoran et al [25] investigated the effect of educational intervention on the improvement of MHL in patients with type 2 diabetes in Iran. This study demonstrated the effectiveness of educational interventions in improving MHL, although the authors did not provide any analysis of the MHL status of the participants [25].…”
Section: Discussionmentioning
confidence: 99%
“…In this trial the most common chronic diseases among teachers were diabetes mellitus, however, the analysis revealed no signi cant association between MHL and chronic illnesses. Karimpour et al in their recent study shown that people with diabetes and limited mental health literacy had signi cantly more incidence of inadequate glycemic control and lacking care for self [23]. The relationship between MHL and chronic illnesses such as hypertension, diabetes, and chronic pain following injuries; are yet to be studied and explored in more depth.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that 1-year follow-up may none enough long for severe change or difference in MSD of some body parts. [ 30 31 ]…”
Section: Discussionmentioning
confidence: 99%